The Importance of Human Resource Information System (HRIS) In Organization - Annisa, Zulfa Nur (International Journal of Engineering and Emerging Technology; Vol 6 No 2 (2021): July - December 2021, 2022)
Human Resource Information Systems is a systematic procedure regarding the collection, storage, maintenance, retrieval and validation of various data required by the organization in the working unit (Handoko, 2008: 237). HRIS is essential for any good organization to ensure effective people management and to get a competitive edge in the corporate world accordingly. This study aims to determine the importance of human resource information systems (HRIS) in organizations. This research uses qualitative research. In collecting data, the researcher uses the literacy method where the method is carried out by analyzing and describing existing information to obtain data accurately according to existing facts.